Mecamylamine treatment for alcohol dependence: a randomized controlled trial. (12th October 2017) - Petrakis, Ismene L.; Ralevski, Elizabeth; Gueorguieva, Ralitza; O'Malley, Stephanie S.; Arias, Albert; Sevarino, Kevin A.; Jane, Jane S.; O'Brien, Erin; Krystal, John H.
Abstract: Background and aims: The nicotinic acetylcholine receptor antagonist, mecamylamine, is a potential novel pharmacotherapy for alcohol use disorder. The aims were to compare alcohol consumption between mecamylamine and placebo and test if smoking status modified treatment effects. Design: Out‐patient, randomized, double‐blind clinical trial for 12 weeks of treatment with mecamylamine (10 mg) ( n = 65) versus placebo ( n = 63). Setting: Connecticut, USA. Participants: Individuals had current alcohol dependence ( n = 128), had an average age of 48.5 [standard deviation (SD) = 9.4], 110 (85.9%) were men, and included 74 smokers (57.8%) and 54 non‐smokers (42.2%). Participants were randomized to mecamylamine 10 mg per day or placebo. All subjects also received medical management therapy administered by trained research personnel. Measurements: Primary outcome was percentage of heavy drinking days during the last month of treatment; other outcomes included drinking days, drinks per drinking days, alcohol craving, smoking, symptoms of nicotine withdrawal and side effects. Findings: There were no significant differences in the percentage of heavy drinking days at 3 months between the mecamylamine (mean = 18.4, SD = 29.0) and placebo treatment groups (mean = 20.4, SD = 29.2) [ F 1, 100 = 1.3, P = 0.25; effect size d = 0.07; mean difference = 2.06, 95% confidence interval (CI) = −8.96 to 13.08]. There were no significant differences in percentage of drinking days or in drinks per drinking day at month 3 between the mecamylamine and placebo groups; there were no significant interactions. Conclusions: Mecamylamine 10 mg per day did not reduce alcohol consumption significantly in treatment‐seeking smokers and non‐smokers with alcohol use disorder.